Hsp104 N‐terminal domain interaction with substrates plays a regulatory role in protein disaggregation. (30th March 2022) - Harari, Anna; Zoltsman, Guy; Levin, Tal; Rosenzweig, Rina
Abstract : Heat shock protein 104 (Hsp104) protein disaggregases are powerful molecular machines that harness the energy derived from ATP binding and hydrolysis to disaggregate a wide range of protein aggregates and amyloids, as well as to assist in yeast prion propagation. Little is known, however, about how Hsp104 chaperones recognize such a diversity of substrates, or indeed the contribution of the substrate‐binding N‐terminal domain (NTD) to Hsp104 function. Herein, we present a NMR spectroscopy study, which structurally characterizes the Hsp104 NTD‐substrate interaction. We show that the NTD includes a substrate‐binding groove that specifically recognizes exposed hydrophobic stretches in unfolded, misfolded, amyloid and prion substrates of Hsp104. In addition, we find that the NTD itself has chaperoning activities which help to protect the exposed hydrophobic regions of its substrates from further misfolding and aggregation, thereby priming them for threading through the Hsp104 central channel. We further demonstrate that mutations to this substrate‐binding groove abolish Hsp104 activation by client proteins and keep the chaperone in a partially inhibited state. The Hsp104 variant with these mutations also exhibited significantly reduced disaggregation activity and cell survival at extreme temperatures. Together, our findings provide both a detailed characterization of the NTD‐substrate complex and insight into the functional regulatory role of the NTD in protein disaggregation and yeast thermotolerance. Abstract : Heat shock protein 104 (Hsp104) chaperones form powerful molecular machines, capable of disaggregating a wide range of protein aggregates and amyloid fibres. Hsp104 N‐terminal domain contains a hydrophobic substrate‐binding groove that enables the chaperone to interact with unfolded, misfolded, amyloid and prion substrates. Mutations to this groove abolish Hsp104 activation by client proteins and keep the chaperone in a partially inhibited state, significantly reducing Hsp104 disaggregation activity and cell survival at extreme temperatures.